2007
DOI: 10.1002/ijc.22756
|View full text |Cite
|
Sign up to set email alerts
|

Family history of gallstones and the risk of biliary tract cancer and gallstones: A population‐based study in Shanghai, China

Abstract: Cancers of the biliary tract arise from the gallbladder, extrahepatic bile ducts and ampulla of Vater. Although relatively uncommon, the incidence of biliary tract cancer rose more than 100% in Shanghai, China between 1972 and1994. Gallstones are the predominant risk factor for biliary tract cancers, with over 60% of the cancer cases having gallstones. A familial tendency to gallstones has been reported and may elevate the risk of gallbladder cancer further. As part of a large population-based case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 29 publications
(33 reference statements)
0
78
1
1
Order By: Relevance
“…Details of the study have been reported elsewhere (Hsing et al, 1998(Hsing et al, , 2007a. Patients with primary biliary cancer 156) newly diagnosed between June 1997 and May 2001 were identified through a rapid-reporting system established between the Shanghai Cancer Institute and 42 collaborating hospitals in urban Shanghai.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the study have been reported elsewhere (Hsing et al, 1998(Hsing et al, , 2007a. Patients with primary biliary cancer 156) newly diagnosed between June 1997 and May 2001 were identified through a rapid-reporting system established between the Shanghai Cancer Institute and 42 collaborating hospitals in urban Shanghai.…”
Section: Methodsmentioning
confidence: 99%
“…3,9,10 Briefly, cancer cases were identified by a rapid reporting system established by the Shanghai Cancer Institute (SCI) and 42 collaborating hospitals in Shanghai. Through this system we identified more than 95% of all incident biliary tract cancer cases (ICD9 code 156) diagnosed among Shanghai residents between June 1997 and May 2001.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The role of genetic factors in biliary tract cancers and stones has been suggested by reports of ethnic and familial predisposition, but the genetic pathways are unclear (1,15). Although some gene variants in the lipid metabolism pathway have been linked to gallstones (16,17), few studies have examined their role in biliary tract cancers.…”
Section: Introductionmentioning
confidence: 99%